Metagenomics-based characterization of fecal microbiome and resistome of laying hens during the production cycle - Gao, Ying-Qian; Hou, Qing-Yu; Hou, Xin-Wen; Wei, Yong-Jie; Shang, Kai-Meng; Ma, He; Geng, Hong-Li; Liu, Rui; Yang, Li-Hua; Elsheikha, Hany M.; Ni, Hong-Bo; Huang, Yu-Feng (Frontiers in Veterinary Science, 2026)
The extensive use of antimicrobials in livestock has accelerated the emergence of antimicrobial resistance (AMR), raising serious global concerns. Poultry feces are recognized as important reservoirs of antibiotic resistance genes (ARGs) and their associated mobile genetic elements (MGEs); however, the microbial community characteristics and ARG profiles of laying hens across different laying stages remain poorly understood. In this study, 40 fecal samples were collected from laying hens at five sampling points, including the early laying stage (HE), three peak laying stages (HPI, HPII, and HPIII), and the late laying stage (HL), with eight randomly selected samples per stage. Shotgun metagenomic sequencing was conducted to characterize the taxonomic structure and functional profiles of the intestinal microbiota and to systematically analyze the diversity and distribution patterns of ARGs. The results showed that most ARGs were harbored by bacteria belonging to the phyla Pseudomonadota and Bacillota, with Escherichia coli serving as the primary carrier of antibiotic resistance genes. Moreover, significant correlations were observed between the co-abundance and co-occurrence of ARGs and MGEs, suggesting that MGEs play a key role in facilitating ARG dissemination. Overall, these findings provide novel insights into the prevalence of ARGs in laying hens across different laying stages and may inform strategies to mitigate the spread of antimicrobial resistance in poultry production systems.